Worldview and personality in the context of philosophical understanding of human self-actualization - Medzhidova, N. (Karagandy University of the name of acad. E.A. Buketov, 2025)
The article deals with issues related to the philosophical understanding of human transformation in the conditions of modern reality. Stating that there is a crisis in the spiritual development of mankind, the author offered his vision of what can contribute to its overcoming. Turning to the experience of philosophical anthropology, the author analyzed the correlation between individuality, personality and worldview. Obviously, these concepts are related to the social activity of the subject and are based on the dialectics of the subjective and objective. Compared to individuality, personality is distinguished by greater activity, aspiration to selfactualization, responsibility for the consequences of its activity. At the same time, the activity of a personality should have a creative character. In the context of this philosophical approach, which integrates many realities of human existence, a person appears as an ontological reality, as a personality, the creative beginning of social practice and history. The being space of a person is interpreted as a subjective-objective reality or a unique integrity of interdependent phenomena of a person’s inner world, his or her worldview searches and expectations.
Keywords: meaning of life; self-actualization; personality; subject; man; worldview